Sustainability Accounting and Investment Decision: A Systematic Literature Review - Diva Bestiaulia; Aang Munawar; Tri Marlina; Arief Fahmie (Program Vokasi dan LPPM IBI Kesatuan, 2026)
This study conducts a comprehensive systematic literature review (SLR) to examine the relationship between sustainability accounting and investment decision-making. Amid growing global attention to environmental, social, and governance (ESG) issues, the relevance of sustainability accounting in shaping investment practices has intensified. By synthesizing scholarly publications from 1990 to 2025, the review identifies prevailing themes, theoretical perspectives, and methodological patterns. The findings reveal a significant rise in research interest post-2015 and underscore the interdisciplinary nature of the field, spanning business, environmental science, and economics. Despite substantial progress, challenges persist in standardizing sustainability disclosures, addressing regional imbalances, and integrating technological innovations. The study concludes with managerial implications and proposes future research directions to better align sustainability reporting with investment decision-making imperatives. Keywords: sustainability accounting, investment decision, ESG, systematic literature review, sustainability disclosure, sustainable finance.